Digital educational games in primary education: Revisiting the results of the research projects of the ETiE initiative - Fokides, Emmanuel (Epistemological Approaches to Digital Learning in Educational Contexts, 2020)
Emerging Technologies in Education (ETiE) main objective is to examine the results of the educational uses of emerging technologies in primary and high school settings. For example, ETiE examined the educational uses of drones, virtual reality, 3D multi-user virtual environments, and augmented reality. Young people spend a substantial part of their leisure time by playing digital games, which are the predominant entertainment medium even of very young children. Students are increasingly dependent on technology for information retrieval/exchange and for communicating. Reasonably enough, appealing digital environments, such as digital educational games (DEGs), are compatible with their skills and interests. In the last two projects, the students’ games were evaluated by analysing their content both in terms of programming and game design adequacy. Students’ interest may have been intensified by the fact that the games included scoring systems, which “rewarded” them upon their successful completion of a task.